The spatial expression of informal livelihoods an examination of charcoal production in Tondo, Manila and resettlement - Sicam, Olivia Alma G. (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2021)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/8566/7503